p-cymene impairs SARS-CoV-2 and Influenza A (H1N1) viral replication: In silico predicted interaction with SARS-CoV-2 nucleocapsid protein and H1N1 nucleoprotein - Panagiotopoulos, Athanasios; Tseliou, Melpomeni; Karakasiliotis, Ioannis; Kotzampasi, Danai Maria; Daskalakis, Vangelis; Kesesidis, Nikolaos; Notas, George; Lionis, Christos D.; Kampa, Marilena; Pirintsos, Stergios; Sourvinos, George; Castanas, Elias (My University, 2021)
Therapeutic regimens for the COVID-19 pandemics remain unmet. In this line, repurposing of existing drugs against known or predicted SARS-CoV-2 protein actions have been advanced, while natural products have also been tested. Here, we propose that p-cymene, a natural monoterpene, can act as a potential novel agent for the treatment of SARS-CoV-2-induced COVID-19 and other RNA-virus-induced diseases (influenza, rabies, Ebola). We show by extensive molecular simulations that SARS-CoV-2 C-terminal structured domain contains a nuclear localization signal (NLS), like SARS-CoV, on which p-cymene binds with low micromolar affinity, impairing nuclear translocation of this protein and inhibiting viral replication, as verified by preliminary in vitro experiments. A similar mechanism may occur in other RNA-viruses (influenza, rabies and Ebola), also verified in vitro for influenza, by interaction of p-cymene with viral nucleoproteins, and structural modification of their NLS site, weakening its interaction with importin A. This common mechanism of action renders therefore p-cymene as a possible antiviral, alone, or in combination with other agents, in a broad spectrum of RNA viruses, from SARS-CoV-2 to influenza A infections.
Keywords: Ebola; SARS-CoV-2; Importin A; Influenza A; Nucleocapsid protein; Nucleoprotein; p-cymene; Rabies